2021
DOI: 10.1016/j.jdsr.2021.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk indicators for peri-implant diseases: A literature review

Abstract: Peri-implant diseases are known as undesirable conditions that can occur after implant therapy. Although several risk indicators are becoming clear, the causes of peri-implant diseases have not been completely investigated. The purpose of this review was to summarize the prevalence and risk indicators for peri-implant diseases by referring to current papers from various angles. Many studies have reported the varied prevalence of peri-implant mucositis (23.9%–88.0% at the patient level and 9.7%–81.0% at the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 79 publications
(96 reference statements)
0
30
0
Order By: Relevance
“…PIM around the deep mucosal tunnel implant presents delayed disease resolution after non-surgical debridement [ 50 ]. Implant design with an over-contour prosthetic profile also could pose risks for peri-implant health [ 51 , 52 ]. The role of adjunctive treatments in such situations needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…PIM around the deep mucosal tunnel implant presents delayed disease resolution after non-surgical debridement [ 50 ]. Implant design with an over-contour prosthetic profile also could pose risks for peri-implant health [ 51 , 52 ]. The role of adjunctive treatments in such situations needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Further, peri-implant mucositis and peri-implantitis remain an issue for dental implant morbidity and loss. For instance, a recent review reported the prevalence of peri-implant diseases and found that 23.9–88.0% of patients and 9.7–81.0% of implants presented peri-implant mucositis, while 8.9–45.0% of patients and 4.8–23.0% of implants presented peri-implantitis [ 10 ]. Mirroring periodontal disease progression [ 11 ], peri-implant mucositis is the first stage of peri-implant disease, characterized by inflammation of the peri-implant soft tissues without bone loss; whereas peri-implantitis is the later, more chronic phase, characterized by chronic inflammation of the peri-implant mucosa that progressively and irreversibly leads to bone loss, decreased osseointegration and consequently, implant loss [ 2 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, excessive renal glucose reabsorption has been recognized as one of the main pathophysiological disorders in type 2 DM and a specific class of hypoglycemic agents SGLT2 inhibitors is now widely used to mitigate this phenomenon [14], in nerves, heart, and blood vessels [15][16][17][18]. It therefore represents a risk factor for many systemic and local pathologies including peri-implantitis [19][20][21].…”
Section: Introductionmentioning
confidence: 99%